Managing Prognosis in Precision Medicine: Utility, Imagination, and Communication - Rebecca Mueller; Brittany M. Lee; Katharine Press Callahan (MDPI AG, 2023)
Research on how physicians predict and communicate prognosis focuses primarily on end-of-life care. Unsurprisingly, as genomic technology gains traction as a prognostic tool, the focus has also been on terminality, with research focused on how genetic results may be used to terminate pregnancies or redirect care towards palliation for neonates. However, genomic results also have powerful impacts on how patients who live prepare for their futures. Genomic testing provides broad-reaching and early-albeit complex, uncertain, and shifting-prognostic information. In this essay, we argue that as genomic testing occurs earlier and increasingly in a screening context, researchers and clinicians must strive to understand and manage the prognostic implications of results. While our understanding of the psychosocial and communicational aspects of prognosis in symptomatic populations is incomplete, it has progressed further than our understanding in a screening context and therefore provides useful lessons and feasible opportunities for further research. By providing an interdisciplinary and inter-specialty perspective on the psychosocial and communicational aspects of prognosis in genetics, we discuss prognostication with respect to genetics from the neonatal period through adulthood, highlighting medical specialties and patient populations that are especially informative for considering the longitudinal management of prognostic information in genomic medicine.